Genetic diversity and distinctiveness of Chilean Limachino tomato (Solanum lycopersicum L.) reveal an in situ conservation during the 20th century - Donoso, Adolfo; Carrasco, Basilio; Araya, Carolina; Salazar, Erika (Frontiers in Conservation Science, 2023)
Landraces constitute a valuable genetic pool of increased diversity that can be exploited for agriculture sustainability, food security, food quality, and, future yield increments. It also contributes to understanding a species's origin, domestication, population dynamics, and diversity. Chilean tomato germplasm characterization and documentation is scarce. To elucidate its potential and distinctiveness, we assessed the genetic variability between and within accessions of tomato landraces grown in Chile between 1938 and 2016, determining the relationships between them and with some European and USA heirloom varieties. For this purpose, the tomato plants were characterized using 72 descriptors for vegetative and reproductive morphology. In addition, molecular diversity, and the determination of genetic patterns between tomato accessions were made using highly informative SSR markers. Our results indicate that the genetic structure among evaluated accessions is associated with differences between the Chilean landraces grown to 1938 and cultivars grown in Europe and USA. The Chilean cluster presented a high variability. The Limachino tomato landrace is close to Marmande but distinguishable on phenotype and the molecular basis for its private alleles. Being grown in the territory of Limache before 1960 until the present day. Accessions of pink beefsteak tomato grown in Chile to 2015 are distant to the rest of the tomato accessions on morphotype and close in SSR genotype to the materials grown in Chile in 1938, supporting the hypothesis of a pre-green revolution tomato diversification in Chilean territory. Chilean tomato populations may impact breeding programs due to higher variability in yield components. Our results are consistent with other researchers that have proposed Mesoamerica and the Andes Region as tomatoes' primary center of diversity.